Laboratory observations of elasto-acoustic signals of rock fragmentation, fluid-filled cavities formation, stick-slip motion and mass flux dynamics - Alejandra Arciniega-Ceballos; Miguel A. Alatorre-Ibargüengoitia; Bettina Scheu; Gerardo Mendo-Pérez; Donald B. Dingwell (Journal of Volcanology and Geothermal Research, 2026)

Earthworms promote soil organic carbon formation across management histories without stimulating the mineralization of native carbon - Janus den Toonder; Šárka Angst; Jan Frouz; Veronika Jílková; Jaroslav Kukla; Travis B. Meador; Stefan Scheu; Karel Tajovský; Gerrit Angst (Biology and Fertility of Soils, 2026)

Inherent duality of vesiculation kinematics revealed through 4D imaging - Mathieu Colombier; Francisco Cáceres; Janine Birnbaum; Rebecca deGraffenried; Yan Lavallée; Jackie E. Kendrick; Bettina Scheu; Simon Thivet; Pedro Valdivia; Ruben M. Ruhekenya; Christian M. Schlepütz; Jonathan M. Castro; et al. (Journal of Volcanology and Geothermal Research, 2026)

The role of pre-eruptive bubble characteristics in modulating andesitic magma fragmentation - Daniel Weller; Cristian Montanaro; Donald B. Dingwell; Shane Cronin; Bettina Scheu (Bulletin of Volcanology, 2026)
Brittle magmatic fragmentation is pivotal in volcanic eruptions, influencing both eruption dynamics and pyroclast generation. Rapid decompression of a volatile-rich, viscous magma can initiate an explosive phase, which is directly influenced by gas overpressure in bubbles. However, natural systems and their associated bubble textures are rarely homogeneous, meaning that pressure and shear conditions can vary on different scales. Analytical and experimental methods are combined in this study to investigate the influence of vesicle texture on andesitic magma fragmentation. We examined diverse pyroclasts with varying porosity (10–80%) and permeability (10 −16 –10 −11 m 2 ) from the sub-Plinian 1655 CE Burrell eruption of Mt. Taranaki and conducted textural analysis on polished samples representative of the main lithologies. Subsequent fragmentation experiments by rapid decompression enabled evaluation of the fragmentation threshold, and a synchronized high-speed camera facilitated the quantification of fragmentation speed and fracture density. Additionally, particle size distributions of experimental fragments were analysed to evaluate fragmentation efficiency. Burrell pumices show high vesicle number densities with evidence of continuous nucleation and growth patterns and various degrees of coalescence that likely occurred during magma ascent. Correlating the textural investigation with rock fragmentation, we observe that vesicle diameter and coalescence can affect grain size distribution and fracture location, as textural heterogeneities can increase the local permeability, and high vesicle number densities can increase the production of fine ash. These findings contribute to a new conceptual model linking homogeneous bubble textures to increased fine ash production and fracture density, while vesicle coalescence promotes localized pressure loss and production of lapilli-sized fragments. The results of this study augment the established eruptive models of Mt. Taranaki and other similar systems.

The role of submarine volcanism in atmospheric chemistry - M. Colombier; M. Bonifacie; M. Brenna; A. Burke; C. Cimarelli; S.J. Cronin; P. Delmelle; D.B. Dingwell; K-U. Hess; M. Huebsch; T. Kula; F. Latu’ila; et al. (Earth and Planetary Science Letters, 2025)

The viscous-brittle transition in flowing crystal-bearing volcanic dome lavas - Fabian B. Wadsworth; Jérémie Vasseur; Michael J. Heap; Jackie E. Kendrick; Claire E. Harnett; Annabelle Foster; Daniel Weller; Bettina Scheu; Anthony Lamur; Luiz Pereira; Donald B. Dingwell; Yan Lavallée (Journal of Volcanology and Geothermal Research, 2025)

The rheology of rhyolite magma from the IDDP-1 borehole and Hrafntinnuhryggur (Krafla, Iceland) with implications for geothermal drilling - Fabian B. Wadsworth; Jérémie Vasseur; Yan Lavallée; Kai-Uwe Hess; Jackie E. Kendrick; Jonathan M. Castro; Daniel Weidendorfer; Shane M. Rooyakkers; Annabelle Foster; Lucy E. Jackson; Ben M. Kennedy; Alexander R.L. Nichols; et al. (Journal of Volcanology and Geothermal Research, 2024)

Confocal Scanning Laser Microscopic (CSLM) characterization of volcanic rocks - Daniel Weller; Mathieu Colombier; Francisco Cáceres; Jérémie Vasseur; Donald B. Dingwell; Bettina Scheu (Journal of Volcanology and Geothermal Research, 2024)

Climate-dependent plant responses to earthworms in two land-use types - Qun Liu; Nico Eisenhauer; Stefan Scheu; Gerrit Angst; Miriam Bücker; Yuanyuan Huang; Travis B. Meador; Martin Schädler (Oecologia, 2024)
Plant nutrient uptake and productivity are driven by a multitude of factors that have been modified by human activities, like climate change and the activity of decomposers. However, interactive effects of climate change and key decomposer groups like earthworms have rarely been studied. In a field microcosm experiment, we investigated the effects of a mean future climate scenario with warming (+ 0.50 °C to + 0.62 °C) and altered precipitation (+ 10% in spring and autumn, − 20% in summer) and earthworms (anecic—two Lumbricus terrestris , endogeic—four Allolobophora chlorotica and both together within 10 cm diameter tubes) on plant biomass and stoichiometry in two land-use types (intensively used meadow and conventional farming). We found little evidence for earthworm effects on aboveground biomass. However, future climate increased above- (+40.9%) and belowground biomass (+44.7%) of grass communities, which was mainly driven by production of the dominant Festulolium species during non-summer drought periods, but decreased the aboveground biomass (− 36.9%) of winter wheat. Projected climate change and earthworms interactively affected the N content and C:N ratio of grasses. Earthworms enhanced the N content (+1.2%) thereby decreasing the C:N ratio (− 4.1%) in grasses, but only under ambient climate conditions. The future climate treatment generally decreased the N content of grasses (aboveground: − 1.1%, belowground: − 0.15%) and winter wheat (− 0.14%), resulting in an increase in C:N ratio of grasses (aboveground: + 4.2%, belowground: +6.3%) and wheat (+5.9%). Our results suggest that climate change diminishes the positive effects of earthworms on plant nutrient uptakes due to soil water deficit, especially during summer drought.

Reactive phosphorus via simulated lightning discharge: A role for fulgurites in pre-biotic chemistry - A. Zeynep Çalışkanoğlu; Donald B. Dingwell; Corrado Cimarelli; Alessandra S.B. Camara; Hergen Breitzke; Gerd Buntkowsky; Matthew A. Pasek; Dieter Braun; Bettina Scheu; Karan Molaverdikhani (Chemical Geology, 2023)

Three perspectives on the prediction of chemical effects in ecosystems - Anke Schneeweiss; Noël P. D. Juvigny‐Khenafou; Stephen Osakpolor; Andreas Scharmüller; Sebastian Scheu; Verena C. Schreiner; Roman Ashauer; Beate I. Escher; Florian Leese; Ralf B. Schäfer (Global Change Biology, 2023)
The increasing production, use and emission of synthetic chemicals into the environment represents a major driver of global change. The large number of synthetic chemicals, limited knowledge on exposure patterns and effects in organisms and their interaction with other global change drivers hamper the prediction of effects in ecosystems. However, recent advances in biomolecular and computational methods are promising to improve our capacity for prediction. We delineate three idealised perspectives for the prediction of chemical effects: the suborganismal, organismal and ecological perspective, which are currently largely separated. Each of the outlined perspectives includes essential and complementary theories and tools for prediction but captures only part of the phenomenon of chemical effects. Links between the perspectives may foster predictive modelling of chemical effects in ecosystems and extrapolation between species. A major challenge for the linkage is the lack of data sets simultaneously covering different levels of biological organisation (here referred to as biological levels) as well as varying temporal and spatial scales. Synthesising the three perspectives, some central aspects and associated types of data seem particularly necessary to improve prediction. First, suborganism‐ and organism‐level responses to chemicals need to be recorded and tested for relationships with chemical groups and organism traits. Second, metrics that are measurable at many biological levels, such as energy, need to be scrutinised for their potential to integrate across levels. Third, experimental data on the simultaneous response over multiple biological levels and spatiotemporal scales are required. These could be collected in nested and interconnected micro‐ and mesocosm experiments. Lastly, prioritisation of processes involved in the prediction framework needs to find a balance between simplification and capturing the essential complexity of a system. For example, in some cases, eco‐evolutionary dynamics and interactions may need stronger consideration. Prediction needs to move from a static to a real‐world eco‐evolutionary view.

Stratigraphic reconstruction of the Víti breccia at Krafla volcano (Iceland): insights into pre-eruptive conditions priming explosive eruptions in geothermal areas - Cristian Montanaro; Anette Kærgaard Mortensen; Tobias B. Weisenberger; Donald B. Dingwell; Bettina Scheu (Bulletin of Volcanology, 2021)
Krafla central volcano in Iceland has experienced numerous basaltic fissure eruptions through its history, the most recent examples being the Mývatn (1724‒1729) and Krafla Fires (1975–1984). The Mývatn Fires opened with a steam-driven eruption that produced the Víti crater. A magmatic intrusion has been inferred as the trigger perturbing the geothermal field hosting Víti, but the cause(s) of the explosive response remain uncertain. Here, we present a detailed stratigraphic reconstruction of the breccia erupted from Víti crater, characterize the lithologies involved in the explosions, reconstruct the pre-eruptive setting, fingerprint the eruption trigger and source depth, and reveal the eruption mechanisms. Our results suggest that the Víti eruption can be classified as a magmatic-hydrothermal type and that it was a complex event with three eruption phases. The injection of rhyolite below a pre-existing convecting hydrothermal system likely triggered the Víti eruption. Heating and pressurization of shallow geothermal fluid initiated disruption of a scoria cone “cap” via an initial series of small explosions involving a pre-existing altered weak zone, with ejection of fragments from at least 60-m depth. This event was superseded by larger, broader, and dominantly shallow explosions (~ 200 m depth) driven by decompression of hydrothermal fluids within highly porous, poorly compacted tuffaceous hyaloclastite. This second phase was triggered when pressurized fluids broke through the scoria cone complex “cap”. At the same time, deep-rooted explosions (~ 1-km depth) began to feed the eruption with large inputs of fragmented rhyolitic juvenile and host rock from a deeper zone. Shallow explosions enlarging the crater dominated the final phase. Our results indicate that at Krafla, as in similar geological contexts, shallow and thin hyaloclastite sequences hosting hot geothermal fluids and capped by low-permeability lithologies (e.g. altered scoria cone complex and/or massive, thick lava flow sequence) are susceptible to explosive failure in the case of shallow magmatic intrusion(s).

Diversity and functional structure of soil animal communities suggest soil animal food webs to be buffered against changes in forest land use - Melanie M. Pollierer; Bernhard Klarner; David Ott; Christoph Digel; Roswitha B. Ehnes; Bernhard Eitzinger; Georgia Erdmann; Ulrich Brose; Mark Maraun; Stefan Scheu (Oecologia, 2021)
Forest soil and litter is inhabited by a diverse community of animals, which directly and indirectly rely on dead organic matter as habitat and food resource. However, community composition may be driven by biotic or abiotic forces, and these vary with changes in habitat structure and resource supply associated with forest land use. To evaluate these changes, we compiled comprehensive data on the species composition of soil animal communities and environmental factors in forest types varying in land-use intensity in each of three regions in Germany, i.e., coniferous, young managed, old managed, and unmanaged beech forests. Coniferous forests featured high amounts of leaf litter and low microbial biomass concentrations contrasting in particular unmanaged beech forests. However, soil animal diversity and functional community composition differed little between forest types, indicating resilience against disturbance and forest land use. Structural equation modelling suggested that despite a significant influence of forest management on resource abundance and quality, the biomass of most soil fauna functional groups was not directly affected by forest management or resource abundance/quality, potentially because microorganisms hamper the propagation of nutrients to higher trophic levels. Instead, detritivore biomass depended heavily on soil pH. Macrofauna decomposers thrived at high pH, whereas mesofauna decomposers benefitted from low soil pH, but also from low biomass of macrofauna decomposers, potentially due to habitat modification by macrofauna decomposers. The strong influence of soil pH shows that decomposer communities are structured predominantly by regional abiotic factors exceeding the role of local biotic factors such as forest type.

Hydrothermal eruption dynamics reflecting vertical variations in host rock geology and geothermal alteration, Champagne Pool, Wai-o-tapu, New Zealand - Anna Gallagher; Cristian Montanaro; Shane Cronin; Bradley Scott; Donald B. Dingwell; Bettina Scheu (Bulletin of Volcanology, 2020)
Hydrothermal eruptions are characterised by violent explosions ejecting steam, water, mud, and rock. They pose a risk to tourism and the operation of power plants in geothermal areas around the world. Large events with a severe destructive threat are often intensified by the injection of magmatic fluids along faults and fractures within volcano-tectonic rifting environments, such as the Taupo Volcanic Zone. How these hydrothermal eruptions progress, how craters form and the scale of ejecta impacts, are all influenced by the local geology and reservoir hydrology. By analysing breccia lithology, undisturbed strata proximal to the explosion sites, and conducting tailored decompression experiments, we elucidate the eruption sequence that formed Champagne Pool, Wai-o-tapu, New Zealand. This iconic touristic site was formed by a violent hydrothermal eruption at ~ 700 years B.P. Samples from undisturbed drill cores and blocks ejected in the eruption were fragmented in shock-tube experiments under the moderate pressure/temperature conditions estimated for this system (3–4 MPa, 210–220 °C). Our results show that this was a two-phase eruption. It started with an initial narrow jetting of deep-sourced lithologies, ejecting fragments from at least a 110-m depth. This event was overtaken by a larger, broader, and dominantly shallower eruption driven by decompression of much more geothermal fluid within a soft and porous ignimbrite horizon. The second phase was triggered once the initial, deeper-sourced eruption broke through a strong silicified aquitard cap. The soft ignimbrite collapsed during the second-phase eruption into the crater, to repeatedly choke the explosions causing short-term pressure rises that triggered ongoing deeper-sourced eruptions. The eruption spread laterally also by exploiting a local fault. These results are relevant for hydrothermal eruption hazard scenarios in environments where strong vertical variations in rock strength and porosity occur.

In situ observation of the percolation threshold in multiphase magma analogues - M. Colombier; F. B. Wadsworth; B. Scheu; J. Vasseur; K. J. Dobson; F. Cáceres; A. Allabar; F. Marone; C. M. Schlepütz; D. B. Dingwell (Bulletin of Volcanology, 2020)
Magmas vesiculate during ascent, producing complex interconnected pore networks, which can act as outgassing pathways and then deflate or compact to volcanic plugs. Similarly, in-conduit fragmentation events during dome-forming eruptions create open systems transiently, before welding causes pore sealing. The percolation threshold is the first-order transition between closed- and open-system degassing dynamics. Here, we use time-resolved, synchrotron-source X-ray tomography to image synthetic magmas that go through cycles of opening and closing, to constrain the percolation threshold Φ C at a range of melt crystallinity, viscosity and overpressure pertinent to shallow magma ascent. During vesiculation, we observed different percolative regimes for the same initial bulk crystallinity depending on melt viscosity and gas overpressure. At high viscosity (> 10 6 Pa s) and high overpressure (~ 1–4 MPa), we found that a brittle-viscous regime dominates in which brittle rupture allows system-spanning coalescence at a low percolation threshold ( Φ C ~0.17) via the formation of fracture-like bubble chains. Percolation was followed by outgassing and bubble collapse causing densification and isolation of the bubble network, resulting in a hysteresis in the evolution of connectivity with porosity. At low melt viscosity and overpressure, we observed a viscous regime with much higher percolation threshold ( Φ C > 0.37) due to spherical bubble growth and lower degree of crystal connection. Finally, our results also show that sintering of crystal-free and crystal-bearing magma analogues is characterised by low percolation thresholds ( Φ C = 0.04 – 0.10). We conclude that the presence of crystals lowers the percolation threshold during vesiculation and may promote outgassing in shallow, crystal-rich magma at initial stages of Vulcanian and Strombolian eruptions.

Diversity of soluble salt concentrations on volcanic ash aggregates from a variety of eruption types and deposits - Mathieu Colombier; Sebastian B. Mueller; Ulrich Kueppers; Bettina Scheu; Pierre Delmelle; Corrado Cimarelli; Shane J. Cronin; Richard J. Brown; Manuela Tost; Donald B. Dingwell (Bulletin of Volcanology, 2019)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Hydrothermal activity and subsoil complexity: implication for degassing processes at Solfatara crater, Campi Flegrei caldera - Cristian Montanaro; Klaus Mayer; Roberto Isaia; Marceau Gresse; Bettina Scheu; Tim I. Yilmaz; Jean Vandemeulebrouck; Tullio Ricci; Donald B. Dingwell (Bulletin of Volcanology, 2017)

Phreatic activity and hydrothermal alteration in the Valley of Desolation, Dominica, Lesser Antilles - Klaus Mayer; Bettina Scheu; Tim I. Yilmaz; Cristian Montanaro; H. Albert Gilg; Stefanie Rott; Erouscilla P. Joseph; Donald B. Dingwell (Bulletin of Volcanology, 2017)

Evolution of a small hydrothermal eruption episode through a mud pool of varying depth and rheology, White Island, NZ - M. J. Edwards; B. M. Kennedy; A. D. Jolly; B. Scheu; P. Jousset (Bulletin of Volcanology, 2017)

MeMoVolc report on classification and dynamics of volcanic explosive eruptions - C. Bonadonna; R. Cioni; A. Costa; T. Druitt; J. Phillips; L. Pioli; D. Andronico; A. Harris; S. Scollo; O. Bachmann; G. Bagheri; S. Biass; et al. (Bulletin of Volcanology, 2016)

Conduit margin heating and deformation during the AD 1886 basaltic Plinian eruption at Tarawera volcano, New Zealand - Jenny Schauroth; Fabian B. Wadsworth; Ben Kennedy; Felix W. von Aulock; Yan Lavallée; David E. Damby; Jérémie Vasseur; Bettina Scheu; Donald B. Dingwell (Bulletin of Volcanology, 2016)

Plant diversity drives soil microbial biomass carbon in grasslands irrespective of global environmental change factors - Madhav Prakash Thakur; Alexandru Milcu; Pete Manning; Pascal A. Niklaus; Christiane Roscher; Sally Power; Peter B. Reich; Stefan Scheu; David Tilman; Fuxun Ai; Hongyan Guo; Rong Ji; et al. (Global Change Biology, 2015)
Soil microbial biomass is a key determinant of carbon dynamics in the soil. Several studies have shown that soil microbial biomass significantly increases with plant species diversity, but it remains unclear whether plant species diversity can also stabilize soil microbial biomass in a changing environment. This question is particularly relevant as many global environmental change ( GEC ) factors, such as drought and nutrient enrichment, have been shown to reduce soil microbial biomass. Experiments with orthogonal manipulations of plant diversity and GEC factors can provide insights whether plant diversity can attenuate such detrimental effects on soil microbial biomass. Here, we present the analysis of 12 different studies with 14 unique orthogonal plant diversity × GEC manipulations in grasslands, where plant diversity and at least one GEC factor (elevated CO 2 , nutrient enrichment, drought, earthworm presence, or warming) were manipulated. Our results show that higher plant diversity significantly enhances soil microbial biomass with the strongest effects in long‐term field experiments. In contrast, GEC factors had inconsistent effects with only drought having a significant negative effect. Importantly, we report consistent non‐significant effects for all 14 interactions between plant diversity and GEC factors, which indicates a limited potential of plant diversity to attenuate the effects of GEC factors on soil microbial biomass. We highlight that plant diversity is a major determinant of soil microbial biomass in experimental grasslands that can influence soil carbon dynamics irrespective of GEC .

Sediment transport dynamics near a river inflow in a large alpine lake - K. R. Scheu; D. A. Fong; S. G. Monismith; O. B. Fringer (Limnology and Oceanography, 2015)
Sediment dynamics were investigated in Lake Maggiore, Italy, with field observations from October to mid‐December 2012. Three moorings were deployed in Pallanza Bay, a small embayment on the western side of the lake near the Toce River inflow, to measure temperature and currents throughout the water column and suspended sediment concentration (SSC) was estimated with acoustic instrumentation. River intrusions are shown to dominate observed SSC, although a small amount of sediment resuspension was observed at the site of the shallowest mooring during a large wind event that produced strong upwelling of the thermocline followed by downwelling. Although vertical turbulent sediment flux is typically assumed to indicate resuspension and the upward transport of sediment ( ), downward turbulent sediment flux was observed ( ) near the bed during the largest observed intrusion event. The downward turbulent sediment flux significantly contributes to net deposition rates, which are one order of magnitude larger than rates of erosion measured during the two major events observed. Horizontal transport of sediment occurs in vertically confined layers due to buoyancy‐driven intrusions. Beneath the intrusions, sediment settles out of the water column at settling rates that appear to be constant with depth based on acoustic Doppler current profiler backscatter measurements. The effective settling velocities needed to produce the observed vertical transport of SSC during an inflow intrusion are one order of magnitude larger than those due to the Stokes settling velocity ( ) alone. Particle flocculation and possible convective instabilities may play a role in generating the large observed effective settling rates.

Effects of prey quality and predator body size on prey DNA detection success in a centipede predator - B. Eitzinger; E. M. Unger; M. Traugott; S. Scheu (Molecular Ecology, 2014)
Predator body size and prey quality are important factors driving prey choice and consumption rates. Both factors might affect prey detection success in PCR ‐based gut content analysis, potentially resulting in over‐ or underestimation of feeding rates. Experimental evidence, however, is scarce. We examined how body size and prey quality affect prey DNA detection success in centipede predators. Due to metabolic rates increasing with body size, we hypothesized that prey DNA detection intervals will be shorter in large predators than in smaller ones. Moreover, we hypothesized that prey detection intervals of high‐quality prey, defined by low carbon‐to‐nitrogen ratio will be shorter than in low‐quality prey due to faster assimilation. Small, medium and large individuals of centipedes L ithobius spp. ( L ithobiidae, C hilopoda) were fed C ollembola and allowed to digest prey for up to 168 h post‐feeding. To test our second hypothesis, medium‐sized lithobiids were fed with either D iptera or L umbricidae. No significant differences in 50% prey DNA detection success time intervals for a 272‐bp prey DNA fragment were found between the predator size groups, indicating that body size does not affect prey DNA detection success. Post‐feeding detection intervals were significantly shorter in Lumbricidae and Diptera compared to Collembola prey, apparently supporting the second hypothesis. However, sensitivity of diagnostic PCR differed between prey types, and quantitative PCR revealed that concentration of targeted DNA varied significantly between prey types. This suggests that both DNA concentration and assay sensitivity need to be considered when assessing prey quality effects on prey DNA detection success.

Lack of energetic equivalence in forest soil invertebrates - Roswitha B. Ehnes; Melanie M. Pollierer; Georgia Erdmann; Bernhard Klarner; Bernhard Eitzinger; Christoph Digel; David Ott; Mark Maraun; Stefan Scheu; Ulrich Brose (Ecology, 2014)
Ecological communities consist of small abundant and large non‐abundant species. The energetic equivalence rule is an often‐observed pattern that could be explained by equal energy usage among abundant small organisms and non‐abundant large organisms. To generate this pattern, metabolism (as an indicator of individual energy use) and abundance have to scale inversely with body mass, and cancel each other out. In contrast, the pattern referred to as biomass equivalence states that the biomass of all species in an area should be constant across the body‐mass range. In this study, we investigated forest soil communities with respect to metabolism, abundance, population energy use, and biomass. We focused on four land‐use types in three different landscape blocks (Biodiversity Exploratories). The soil samples contained 870 species across 12 phylogenetic groups. Our results indicated positive sublinear metabolic scaling and negative sublinear abundance scaling with species body mass. The relationships varied mainly due to differences among phylogenetic groups or feeding types, and only marginally due to land‐use type. However, these scaling relationships were not exactly inverse to each other, resulting in increasing population energy use and biomass with increasing body mass for most combinations of phylogenetic group or feeding type with land‐use type. Thus, our results are mostly inconsistent with the classic perception of energetic equivalence, and reject the biomass equivalence hypothesis while documenting a specific and nonrandom pattern of how abundance, energy use, and biomass are distributed across size classes. However, these patterns are consistent with two alternative predictions: the resource‐thinning hypothesis, which states that abundance decreases with trophic level, and the allometric degree hypothesis, which states that population energy use should increase with population average body mass, due to correlations with the number of links of consumers and resources. Overall, our results suggest that a synthesis of food web structures with metabolic theory may be most promising for predicting natural patterns of abundance, biomass, and energy use.

Magmatic architecture of dome-building eruptions at Volcán de Colima, Mexico - Yan Lavallée; N. R. Varley; M. A. Alatorre-Ibargüengoitia; K.-U. Hess; U. Kueppers; S. Mueller; D. Richard; B. Scheu; O. Spieler; D. B. Dingwell (Bulletin of Volcanology, 2012)

Detection of Pathogenic Yersinia enterocolitica in Meat using Real-Time PCR - M. Fredriksson-Ahomaa; B. Hartmann; P. Scheu; A. Stolle (Journal of Consumer Protection and Food Safety, 2007)

Earthworm invasion into previously earthworm-free temperate and boreal forests - Lee E. Frelich; Cindy M. Hale; Stefan Scheu; Andrew R. Holdsworth; Liam Heneghan; Patrick J. Bohlen; Peter B. Reich (Biological Invasions, 2006)

Dynamics of explosive volcanism at Unzen volcano: an experimental contribution - Bettina Scheu; Oliver Spieler; Donald B. Dingwell (Bulletin of Volcanology, 2006)

Permeability and degassing of dome lavas undergoing rapid decompression: An experimental determination - Sebastian Mueller; Oleg Melnik; Oliver Spieler; Bettina Scheu; Donald B. Dingwell (Bulletin of Volcanology, 2005)